Hubungan Profil Lipid dengan Kejadian Ulkus Kaki Diabetik pada Pasien Diabetes Melitus Tipe 2 RSUP dr. Mohammad Hoesin Palembang - Sinulingga, Sadakata; Kohar, Evlin; Subandrate, Subandrate (Fakultas Kedokteran Universitas Sriwijaya, 2018)
Diabetic foot ulcersare long-term complications of diabetes mellitus that may increase morbidity and mortality, also reduce the quality of life of the patients. One of the causes of diabetic foot ulcers is peripheral arterial disease due to dyslipidemia. This study was conducted to determine the relationships of lipid profile with diabetic foot ulcers in patients with type 2 diabetes mellitus. Analytical observational study with cross-sectional design was conducted in 69 diabetic patients. Data was retrieved secondarily by observing the medical records. Total cholesterol, triglycerides, LDL, HDL, and consumption of lipid-lowering drugs of the patients were all recorded. Documented variables were analyzed using Fisher Exact test if Chi-square test criterias were not fulfilled. There was a significant association between diabetic foot ulcers with total cholesterol (p=0,001) and HDL (p=0,015), while triglycerides (p=0,393) and LDL (p=0,176) did not have a significant association with diabetic foot ulcers.Multivariable logistic regression identified HDL (B=2,221, S.E.=1,131, Wald=3,855, p=0,050, exp(B)=9,220 IK95% 1,004–84,691)as the most influential lipid profile fraction to the incident diabetic foot ulcers. Total cholesterol and HDL had a significant association with diabetic foot ulcers. The most influential lipid profile fraction to the incident diabetic foot ulcers is HDL.